Perceptions and Experiences of First Sexual Intercourse in Australian Adolescent Females - Skinner, R. S; Smith, J.; Fenwick, Jennifer; Fyfe, Susan; Hendriks, J. (Elsevier, 2008)
To better understand the factors that influence the initiation of first intercourse among adolescent females and to explore the context in which this occurs.A purposive sample of sexually active female teenagers aged between 14 and 19 years were recruited from sexual and reproductive health clinics across the Perth metropolitan area. Sixty-eight in-depth, semistructured interviews were conducted. Thematic analysis was employed to analyze the narrative data. Meanings and interpretations that emerged were constantly verified through subsequent inquiry.The degree of personal control over the factors that led to their first experience of intercourse determined how teenagers reflected upon the experience. Those who were "ready" were more likely to have delayed intercourse until they were comfortable with both when and with whom this occurred. In contrast, conforming to peer norms, coercion from sexual partners and being intoxicated were common reasons for premature and unwanted first experience of sexual intercourse.The explorative approach used in this study deepens current understanding of the factors influencing and associated with intercourse initiation, and how these reflect different aspects of adolescent development. In particular, the role of young peoples' sociocultural environment, including peer interaction and alcohol intoxication, alongside pressure from sexual partners in premature and unwanted sexual activity may assist in informing education intervention of greater personal relevance and impact